Electrochemical Performance of SrWO4 Electrolyte for SOFC - Afif, Ahmed; Radenahmad, Nikdalila; Zaini, Juliana; Mohamed Abdalla, Abdalla; Habibur Rahman, Seikh Mohammad; Nam Cheok, Quentin Hoon; Azad, Abul Kalam (International Journal of Integrated Engineering, 2021)
Scheelite structured SrWO4 material was synthesized by the solid-state sintering method and studied with respect to phase stability and ionic conductivity under condition of technological relevance for SOFC applications. The resulting compound was crystallized in the single phase of tetragonal scheelite structure with the space group of I41/a. Room temperature X-ray diffraction and subsequent Rietveld analysis confirms its symmetry, space group and structural parameters. Analysis by SEM illustrated a highly dense structure. SrWO4 sample shows lower conductivity compared to the traditional BCZY perovskite structured materials. SrWO4 sample exhibited an ionic conductivity of 1.93 × 10−6 S cm-¹ at 1000℃ in dry Ar condition. Since this scheelite type compound demonstrated significant conductivity and a dense microstructure, it could serve in SOFC as a mixed ion-conducting electrolyte.